Predicting Patterns of Problematic Smartphone Use among University Students: A Latent Class Analysis. (25th August 2022) - Parent, Natasha; Bond, Takara; Wu, Amery; Shapka, Jennifer
Abstract : University students are consistently ranked among the highest users of smartphones. As such, recent research has focused on examining the antecedents and consequences of problematic smartphone use among university students. While this work has been instrumental to our understanding of the risk and protective factors of developing problematic smartphone use, it has been largely variable-centered and thus fails to recognize the diversity with which problematic smartphone use is experienced among university students. As such, this study employed a person-centered approach (i.e., latent class analysis) to classify individuals based on patterns of problematic smartphone use feature/symptom cooccurrence among a sample of 403 Canadian university students. The relationships between these subgroups (or classes) and potential covariates (i.e., self-regulation, attachment anxiety, and attachment avoidance) were then examined to gain a more complete understanding of university students' experiences of problematic smartphone use. Three classes of problematic smartphone use were identified: (1) "connected" displaying the features/symptoms of problematic smartphone use associated with being constantly connected to smartphones; (2) "problematic" displaying all of the features/symptoms of problematic smartphone use; (3) "distracted" displaying the features/symptoms associated with being distracted by smartphones. Findings indicate that attachment anxiety and avoidance were significantly associated with membership in the most pathological (i.e., "problematic") class, suggesting that this may be an especially important risk factor for developing problematic smartphone use among university students. Moreover, self-regulation was significantly related to membership in the least pathological class (i.e., "connected") suggesting that this may function as an important protective factor in developing more concerning patterns of problematic smartphone use. Findings from this work provide empirical evidence of a heterogeneity in patterns of problematic smartphone use associated with distinct individual-level risk factors. This has important implications for conceptualizations of problematic smartphone use and the development of intervention and prevention efforts.